Nickel titanate (NiTiO3) thin films: RF-sputtering synthesis and investigation of related features for photocatalysis. Issue 18 (18th April 2016) - Ruiz-Preciado, M. A.; Bulou, A.; Makowska-Janusik, M.; Gibaud, A.; Morales-Acevedo, A.; Kassiba, A.
Abstract : Synthesis of photoactive semiconducting oxide NiTiO3 by rf-sputtering from crystalline targets with relevant physical and morphological features for applications in heterogeneous photocatalysis. Abstract : Polycrystalline nickel titanate thin films were deposited on silicon substrates by the radio-frequency (rf) sputtering method using NiTiO3 targets, which in turn were sintered from powders obtained by solid state reaction. The deposition parameters such as rf-powers, partial pressures of argon and oxygen, as well as substrate temperatures were optimized to ensure the homogeneous and stoichiometric composition of NiTiO3 thin films. Post-synthesis annealing at suitable temperatures and time durations was realized to stabilize the ilmenite structure with improved crystalline features deduced from structural and vibrational investigations by using XRD and Raman spectroscopy. The surface roughness and thin film microstructure were characterized by AFM which points out the organisation of the film surface. Representative films with ilmenite structure and defined surface microstructure and optical absorbance were tested as visible light driven heterogeneous photocatalysts for the degradation of organic dyes.